MPLEMENTATION PROFFERING OF CLAIM GUARANTEE HEALTH OF NATIONAL HEALTH IN HOSPITAL ANUTAPURA PALU - Sabriyah Sabriyah; Sudirman Sudirman; Andi Reza Alief Chairin Nor (Promotif : Jurnal Kesehatan Masyarakat, 2017)
The hospital’s claim collectively and billed done to the BPJS of each month,with complete supporting documents i.e copy of BPJS card,prof nurse, letter of statement, the cost of which must be paid. The function of the claims of BPJS is the submission the cost of patient care BPJS participaty from the hospital to the BPJS, previously the cost of patient care in the responsibility by the hospital. The porpuse of research to find out information on filing a claim general hospital of Anutapura palu to BPJS. This research has been carried out in a Hospital Anutapura palu and implemented in june 2016. Type writer this research with a qualitative approach. The study make’s and overview of the complex, researching the words, the detailed report of the views of  respondents, and conduct a study on the situation of the natural. The results showed that the claims of the administration in the hospital Anutapura palu has been running in a coedance with the rules as seen from the claims in the pending was upon agreement of the parties hospital and office of the BPJS that follow the rules No. 28 service system JKN. So based on research it can be deduced that the implementation of the filing the claim of the nation health assurance ( JKN ) in Hospital Anutapura palu are in accoedance with Permenkes No.28 service system ( JKN ). Keyword : Implementation, Claim JKN.